Reporting Practices on Immunosuppression and Rejection Management in Face Transplantation: A Systematic Review - Daneshgaran, Giulia; Stern, Carrie S.; Garfein, Evan S. (Journal of Reconstructive Microsurgery, 2019)
Background Face transplantation is a demanding operation requiring complex planning and expert technical performance. While the documentation of successes of the first transplants is impressive, there are lacunae in reporting of institutional protocols for other critical operation components, namely, immunosuppression, graft surveillance, and management of rejection and graft failure. The purpose of this review is to assess protocol reporting by face transplant teams to determine where we, as a plastic surgery community, can improve.Methods A systematic review of PubMed was conducted to identify literature on face transplants published from November, 2005, starting with the first successful transplant to December, 2018. English-language articles were reviewed for reporting of protocols on antimicrobial prophylaxis, immunosuppression, graft surveillance, and management of rejection and graft failure.Results A total of 44 face transplantation patients were identified. Protocols for antimicrobial prophylaxis, immunosuppressive induction, and maintenance immunosuppression were reported for 61%, 75%, and 73% of patients, respectively. Protocols for graft surveillance and medical management of rejection were reported for 70% of patients in both cases. Surgical salvage strategies to manage graft failure were documented for 43% of patients.Conclusion The current literature on face transplantation does not include consistent reporting on critical aspects of patient care. Medical protocols outlining guidelines for immunosuppression, graft surveillance, and management of rejection and graft failure are the most critical factors determining overall transplant success. However, they are underreported in the literature. Development and communication of standardized protocols is essential to improve patient outcomes and maximize the results of this procedure.
Keywords: face transplantation; rejection management; protocol reporting